Varied presentations of incontinentia pigmenti. (29th September 2015) - Ghaffar, SA; Stephen, J; Brotherton, H; Benton, C; Schofield, O
Abstract : Incontinentia pigmenti (IP) is a rare X-linked dominant genodermatosis with cutaneous, neurological, ophthalmological and dental manifestations. 80% of cases have a deletion mutation in the nuclear factor-κB (NF-κB) essential modulator (NEMO) gene located on chromosome Xq28. This gene is required for activation of the transcription factor NF-κB which is central to many immune, inflammatory and apoptotic pathways. The authors present two cases of IP to demonstrate the varied presenting features of this condition. The first case is a 9-month-old girl who presented mildly unwell, with erythematous lines on her abdomen in a "Chinese-writing" distribution. Further examination showed hyperkeratotic lesions on her calves, and a hyperkeratotic papule and blister which had been present on her hand since birth. Her mother had a history of two spontaneous abortions. She had linear hypopigmentation on the legs and only 16 teeth. A diagnosis was made of a viral exanthem arising on a background of IP. She is now 5 years old and has linear hyperpigmentation on her legs, teeth abnormalities and patchy alopecia. Her mother has a confirmed mutation in the NEMO gene. The second case is a 3-month-old baby girl who had developed seizures on the second day of life. An MRI showed two unusual areas on the lateral ventricle which had been interpreted as small areas of ischaemia. She developed linear erythematous papules, blistering and crusting on her groin and trunk on day 4 and a clinical diagnosis of IP was made. Genetic analysis confirmed a mutation in the NEMO gene. Her mother has no mutation in the NEMO gene. There are four cutaneous stages classically seen in IP from birth: vesicular, verrucous, hyperpigmented and, in adulthood, an atrophic hypopigmented stage. In both of our cases, the presenting features were not the classical cutaneous features of IP: case 1 presented with a viral exanthem within the lines of Blaschko; case 2 presented with neurological involvement. The authors present these two cases of IP as examples of the varied presentations of this condition to increase awareness of possible presenting features of this unusual genodermatosis.